Deep in the jungle of doom - Stine, R. L. (New York : Scholastic, 1996)
The reader decides the course of an adventure in which the narrator becomes separated from a nature study group in South America and falls prey to the terrors of the jungle.
"A Parachute Press book"--T.p. verso.
"An apple paperback.".
4.8
3-6
Keywords: Plot-your-own stories; Adventure and adventurers -- Fiction; Jungles -- Fiction; Plot-your-own stories; Adventure fiction; Jungles -- Fiction; Plot-your-own stories